Some considerations on the use of digital evidence in Labour Law - Ana LAMBELHO (Revista Jurídica Portucalense, 2022)
This communication briefly analyzes the use of digital evidence in the employment relationship, especially the one obtained through electronic messaging. Digital evidence is placed side by side with other means of evidence when it comes to the legal issues that labour courts are called to decide upon ‑ qualification of the contract; working time; overtime work; dismissal; termination of contract by other means, etc.. The use of digital evidence hence requires a closer scrutiny, since its use has become so important why the problem of using electronic documents as a means of proof is so important. In this work, we will review the main aspects on how to present this type of evidence in court, the legality of evidence collection methods and the value of the evidence obtained.